The essential guide to intellectual property - Sinnreich, Aram (Yale University Press, 2019)
This study looks at the origins, evolution, purpose, and limitations of intellectual property. Detailing how intellectual property affects industry, politics, cultural expression, and medical research, the author takes a multidisciplinary approach to uncover what's behind twenty-first century debates about copyright and what the future holds for copyrights, patents, and trademarks. Based on the notion that intellectual property law is not merely a property right but also a mechanism of cultural and economic regulation with significant consequences for democratic institutions, global businesses, arts, and the sciences, the author draws on media studies, communications, law, economics, and cultural studies as he provides a blueprint for understanding intellectual property rights and underlines the important and pervasive role that they play in everyone's lives.